Pengembangan E-modul Berbasis STEAM pada Topik Peredaran Darah Manusia - Esty Setyo Utaminingsih; Tri Joko Raharjo; Ellianawati Ellianawati (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to develop a STEAM-based e-module for mastering the topic of human blood circulation. The developed e-module is named "Radar.â€ "Radar" e-module from the content validity analysis test obtained a content validity value of 0.9167, construct validity of 0.9208, and language validity of 0.8819. The final validity value of the e-module was 0.9065 with valid criteria. The practicality test results get a percentage of 86.67% and are included in the convenience category. Based on the validity and practicality of test results, the "Radar" e-module is feasible and practical to use to improve students' concepts of human blood circulation